Pemakaian Bahasa Indonesia dalam Lirik Lagu Jawa Kontemporer: Studi Awal Kajian Morfologis - Maryani, Zulisih (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Along with the times present contemporary Javanese songs with new music genres, including campursari, dangdut koplo, and hip hop. Contemporary Javanese songs are free songs by combining diatonic and pentatonic tones, without having to fulfill basic rules. By maintaining the authenticity of Javanese lyrics, there is the use of Indonesian in contemporary Javanese song lyrics. This research will examine how the use of Indonesian in contemporary Javanese song lyrics from the morphological aspects, especially those in the form of basic words and affixed words. There are three stages of strategy in this study, namely the stage of data filtering, data analysis, and presentation of the results of data analysis. The selection of data through observation is done using the basic technique, which is tapping. The tapping technique is followed by the advanced technique, which is a competent, free listening technique. The note taking technique as an advanced technique is also carried out to record the results of data listening on the data card in the form of transcription. Data analysis was performed to find out how to use Indonesian in contemporary Javanese song lyrics based on morphological aspects, especially those in the form of basic words and affixed words. It can be described that in addition to maintaining Javanese language, contemporary Javanese song lyrics also use Indonesian to convey expression and achieve aesthetics in song. Morphologically, the form of words used in relation to the use of Indonesian in contemporary Javanese song lyrics is the basic word and affix word. Basic words in the form of words that have not undergone a morphological process. Affixes used in contemporary Javanese song lyrics are suffixes, suffixes, and confixes. The affixes used are ber-, di-, meN-, ter-, and peN-. Suffixes in the form of -an, -ku, -mu, -i, -nya, and -pun. Meanwhile, there are also confixes ke-/-an, peN-/-an, di-/-kan, and meN-/-i.